WORKSHOP KREASI SENI MELIPAT KERTAS DALAM RANGKA PEMBERDAYAAN MASYARAKAT KELURAHAN MALAKA SARI, KECAMATAN DUREN SAWIT, JAKARTA TIMUR - Frida Philiyanti; Viana Meilani Prasetio; Ilmi Fitria Nurdiana; Liviea Aprilia; Reno Farhan Gati (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Negeri Jakarta, 2022)
Abstract Restrictions on activities outside home due to the prolonged pandemic period provided a monotonous atmosphere, not only among housewives but also teenagers. With the government's policy that provides leeway for the community to return activ outside while still prioritizing health protocols seems like a fresh air to find and start their social interactions again. This community service activity aims to introduce one of Japanese culture, namely the art of paper folding or better known as origami. Based on the preliminary survey conducted, it is known that most of the enthusiasts are housewives and teenagers who want to spend their spare time with useful and fun activities. This activity is in the form of intensive training directly guided by an instructor who has experience and has a business in the field of creating the art of folding both paper and cloth. Therefore, the committee limited the training participants to only twenty people, and all of them were domiciled in the Malaka Sari Village, Duren Sawit District, East Jakarta. The training was conducted offline on Sunday, August 7, 2022, at Balai RW 02, Malaka Sari Village. In accordance with the participant's request in the preliminary survey response, the creations made were bookmarks and wall decorations with the theme